2017
DOI: 10.1155/2017/4676724
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Levels of Organochlorine, Organophosphorus, and Pyrethroid Pesticide Residues in Vegetables from Markets in Dar es Salaam by GC-MS

Abstract: This study investigated the levels of pesticides and metabolites in vegetables from major markets in Dar es Salaam city, Tanzania. Samples of fresh cabbage, spinach, and onions from the markets were analysed for pesticide residues. Extraction was performed using acetone followed by dichloromethane : cyclohexane mixture and the extracts were cleaned up using Florisil. The compounds were determined by gas chromatography-mass spectrometry (GC-MS). Pesticides and metabolites were detected in 72.2% of the samples. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
2

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 5 publications
1
26
2
Order By: Relevance
“…Organochlorine pesticides were not detected in the current study which is a good indication that there is a shift from the use of organochlorine pesticides to pyrethroid and organophosphorus pesticides and therefore a reduced risk of negative health effects associated with exposure to organochlorines. Organochlorines were detected in the studies done in Dar es Salaam (Mahugija, Khamis, & Lugwisha, 2017;Ndengerio-Ndossi & Cram, 2005). The organochlorine pesticides were found in foods as reported in 2005 despite the fact that they had been banned from use in agriculture in Tanzania since 1997 due to their long persistence in the environment and bioaccumulation properties (URT, 2005).…”
Section: Pesticide Residue Contents In Ready-to-eat Vegetablesmentioning
confidence: 99%
See 1 more Smart Citation
“…Organochlorine pesticides were not detected in the current study which is a good indication that there is a shift from the use of organochlorine pesticides to pyrethroid and organophosphorus pesticides and therefore a reduced risk of negative health effects associated with exposure to organochlorines. Organochlorines were detected in the studies done in Dar es Salaam (Mahugija, Khamis, & Lugwisha, 2017;Ndengerio-Ndossi & Cram, 2005). The organochlorine pesticides were found in foods as reported in 2005 despite the fact that they had been banned from use in agriculture in Tanzania since 1997 due to their long persistence in the environment and bioaccumulation properties (URT, 2005).…”
Section: Pesticide Residue Contents In Ready-to-eat Vegetablesmentioning
confidence: 99%
“…A study by Ndengario-Ndossi and Cram, (2005) which analysed 33 samples of spinach found that 72.7% of the samples were contaminated with gamma-hexachlorocyclohexane (g-HCH) (0.08 µg kg -1 ), 1,1-dichloro-2,2-bis (p-chlorophenyl) ethylene (pp-DDE) (0.74 µg kg -1 ), dichlorodiphenyltrichloroethane (pp-DDT) (2.15 µg kg -1 ) and chlorpyrifos (0.02µg kg -1 ). Mahugija, Khamis & Lugwisha (2017) analyzed 72 samples of cabbage, onion, and spinach for pesticide residues in which 72.2% of the vegetables were found to be contaminated with DDT and its metabolites, endosulfan, and cypermethrin. However, these two studies were done in Dar es Salaam, which is not a major vegetable producing area in Tanzania.…”
Section: Introductionmentioning
confidence: 99%
“…The lower prevalence in Arusha city compared to Arusha district could be attributed to transport and storage effects. Detection of organochlorine residues in vegetables has also been reported in various literature including studies done in Dar‐es‐Salaam, Tanzania (Mahugija, Khamis, & Lugwisha, ; Ndengerio‐Ndossi & Cram, ), Basque (Lemos, Sampedro, de Ariño, Ortiz, & Barrio, ), and Cameroon (Gimou, Charrondiere, Leblanc, & Pouillot, ). Pyrethroids and organophosphates are reported as the most frequently applied pesticides in vegetable farming (Ngowi et al, ).…”
Section: Resultsmentioning
confidence: 65%
“…The confirmation of the findings was done using gas chromatography-mass spectrometry (Shimadzu GC-MS QP 2010 Ultra equipped with a mass selective detector-MSD, fused silica capillary column Rtx-5MS of 30 m length × 0.25 mm id × 0.25 µm film and an autosampler) at the Chemistry Department, University of Dar es Salaam applying the procedures described by Mahugija et al 15 The GC-MS was performed in splitless injection mode and the mass spectrometer was operated in electron impact (EI) ionization and full scan mode. The calibration/working standard solutions were prepared by dissolving portions of the stock solutions in the same solvents as used for the samples.…”
Section: Gas Chromatographic Analysis Of Samplesmentioning
confidence: 99%
“…Calibration curves were prepared by running series of mixtures of standard solutions and plotting the peak areas against concentrations. Identification of the compounds employed similar procedures to those reported by Mahugija et al 15 that concisely involved checking the matching of the retention times and the mass spectra of the analytes in samples to those of external reference standards that were prepared and run at the same conditions as for the samples. Selected GC-ECD chromatograms are presented in Fig.…”
Section: Gas Chromatographic Analysis Of Samplesmentioning
confidence: 99%